IMPLEMENTASI PROGRAM “AQUA LESTARI” SEBAGAIICORPORATEISOCIAL RESPONSIBILITY (CSR) PTITIRTAIINVESTAMAIAQUAIMAMBAL, BADUNG - Ayuningtyas, Ananda Vidya; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT Corporate Social Responsibility (CSR) is an ongoing commitment by the company or the business world to actJethicallyPandYcontributeCtoNeconomic, social and environmental developmentKfor the local community or the wider community. The Indonesian government has obliged companies to carry out CSR programs. This has been stated in the Undang-Undang Dasar Republik IndonesiaLNo. 40OofI2007IconcerningIlimitedIliabilityicompanies. CSR has now been implemented in many companies in Indonesia. One company that runs the CSR program is PT Tirta Investama AQUA Mambal. ThePpurposePofOthis studyOwasPtoLdetermineLthe implementationLofNtheRAQUA Lestari program as a CSR of PTpTirtaLInvestama AQUA Mambal. ThisYtypeUofEresearchSisXdescriptiveGqualitative.JDataHcollectionVusesIinterviews, observationJandHdocumentation. The result of theLresearchBconductedVat PT Tirta Investama AQUA Mambal is the AQUA Lestari program run by AQUA Mambal itself which is divided into 2, namely Mambal Lestari which focuses on agriculture while Ayung Lestari focuses on conserving water resources. In its implementation, this program has taken into account the concept of 3P (Profit, Planet and People) where the company not only prioritizes profit but also contributes positively to the community. Keywords: CSR, Implementation, Company, Contribution, PT Tirta Investama AQUA Mambal